Multi-functional gene ZNF281 identified as a molecular biomarker in soft tissue regeneration and pan-cancer progression - Hou, Xueying; Luan, Jie; Fu, Su (Frontiers in Genetics, 2023)
Regeneration and tumorigenesis are indicated as related processes, while regeneration leads to life and the outcome of tumorigenesis is death. Here, we show the upregulation of ZNF281 (Zinc finger 281) in both our adipose de novo regeneration model through RNA-seq analysis. And then we validated the upregulation of ZNF281 in adipose regeneration via immunofluorescence. Following that, we found that ZNF281 was upregulated in most types of cancer and related to worse prognosis in 10 tumors. We furtherly investigated the role of ZNF281 in cervical squamous cell carcinoma and endocervical adenocarcinoma (CESC), pancreatic adenocarcinoma (PAAD) and stomach adenocarcinoma (STAD), and confirmed the high accuracy in clinical diagnostic feature. Beyond that, based on these 3 types of cancers, we analyzed the ZNF281 related tumor immune infiltration, DNA methylation sites and finally, built risk prediction models for future disease diagnosis. Taken together, our findings provide new insights into the dual role of ZNF281, and found it was a potential biomarker for regeneration and tumor prognosis.